Suicide in historic cities of a Brazilian state - Beatriz Faria Simões; Luiza Cantão; Nadja Cristiane Lappann Botti (Rev Rene)
Objective: to analyze the suicide rate in historical regions of Minas Gerais, Brazil. Methods: epidemiological study conducted in five historical regions of a Brazilian state. The data used were extracted from the Information Department of the National Health System. Results: the Historical Regions of Demonstrations and Wealth presented higher suicide rates when compared to the state’s rate. In 11 of the 15 years analyzed, the Region of Wealth had rates higher than that of Minas Gerais. Regarding age group, average levels of suicide were found in the age group 20-59 years in 14 years studied. We also identified higher suicide rates among men in the Historical Regions. The most used methods in the Historical Regions were hanging, strangulation and suffocation. Conclusion: the distribution of suicide cases has enabled to understand the epidemiological characteristics of suicide in the Historical Regions of Minas Gerais during the period analyzed.